A Case of New-Onset Obsessive-Compulsive Disorder and Schizophrenia in a 14-Year-Old Male following the COVID-19 Pandemic - Bibawy, Daniel; Barco, Jennyferd; Sounboolian, Yeghia; Atodaria, Priya (Case Reports in Psychiatry, 2023)
The post-COVID-19 era has introduced novel cases of psychiatric complications that are either organic or purely psychological in nature due to social isolation. This report details a case of new-onset obsessive-compulsive disorder (OCD) and schizophrenia following the COVID-19 pandemic. The novelty of this case lies in the onset of the patient’s symptoms in the context of the COVID-19 pandemic, without prior predisposing risks in the environmental, social, or biological aspects. We provided therapeutic treatment to the patient in an inpatient setting, while examining the patient to decipher the root cause of his symptoms. While there is substantial data suggesting exacerbations of OCD during the COVID-19 pandemic in the general population and a new onset of schizophrenia due to the virus itself, very little is known about the prevalence of either OCD or schizophrenia after the pandemic. With this in mind, we hope to provide more information regarding new-onset psychosis and OCD within the adolescent population. A considerable amount of studies and data are needed in this subset of the population.